PREPARASI FENILBUTAZON DALAM PEMBAWA VESIKULAR ETOSOM DENGAN BERBAGAI VARIASI KONSENTRASI FOSFATIDILKOLIN DAN ETANOL - Nur Illiyyin Akib; Suryani Suryani; Halimahtussaddiyah R Halimahtussaddiyah R; Niken Prawesti (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2014)
Phenylbutazone is non steroidal anti-inflammatory drug (NSAID) used  in treatment of joint inflammation such  as  rheumathoid  arthritis.  In  order  to  minimize  irritation  effect  on  gastrointestinal  tract,  the  dose  of phenylbutazone is reduced or administered through transdermal pathways. Flux penetration of drugs across the membrane  can  be  improved  by  using  vesicular  type  of  delivery  system  such  as  ethosome.  This  study  aim  to prepare  phenylbutazone in  ethosome  vesicular  system.  Ethosome vesicular  systems  were prepared  with  various concentrations  of  phosphatidylcholine  (2%  and  3%)  and  ethanol  (30%,  35%,  and  40%).  Vesicles  that  are formed  further  characterized  by  shape,  size  and  entrapment  efficiency.  The  shaped  of  ethosome  produced  is large  unilamellar vesicle.  The size of vesicle  varies  between  0.57 to 0.81  µm  with  the smallest size  on Formula C.  The  highest  entrapment  efficiencies  was  also  on  the  Formula  C  by  59.88%  with  2%  concentration  of phosphatidylcholine and 40% of ethanol. Keywords: phenylbutazone, vesicle, ethosomes.